2024
DOI: 10.1101/2024.04.10.588822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering the phospho-signature induced by hepatitis B virus in primary human hepatocytes

Florentin Pastor,
Emilie Charles,
Lucid Belmudes
et al.

Abstract: Phosphorylation is a major post-translation modification (PTM) of proteins, and small molecules, which is finely tuned by the activity of several hundred kinases and phosphatases. It controls most if not all cellular pathways including anti-viral responses. Accordingly, viruses often induce important changes in the phosphorylation of host factors that can either help or counteract viral replication. Among more than 500 kinases constituting the human kinome only few have been described as important for the Hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 132 publications
0
1
0
Order By: Relevance
“…Therefore, it is possible that a low and transient stimulation of HBx mRNA transcription early upon cccDNA formation may lead to the synthesis of a basal level of HBx sufficient to induce Smc5/6 degradation (72). In this regard, it is interesting to note that in a recent phospho-proteomic analysis we found that DYRK1A was among the top list of kinases whose activity is predicted to be up-regulated upon HBV infection (73).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that a low and transient stimulation of HBx mRNA transcription early upon cccDNA formation may lead to the synthesis of a basal level of HBx sufficient to induce Smc5/6 degradation (72). In this regard, it is interesting to note that in a recent phospho-proteomic analysis we found that DYRK1A was among the top list of kinases whose activity is predicted to be up-regulated upon HBV infection (73).…”
Section: Discussionmentioning
confidence: 99%